2022
DOI: 10.25105/jat.v9i2.14059
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompleksitas Perusahaan, Ukuran Perusahaan, Reputasi Kap, Dan Pandemi Covid-19 Terhadap Audit Delay

Abstract: Penelitian ini bertujuan untuk menguji pengaruh dari kompleksitas perusahaan, ukuran perusahaan, reputasi KAP, dan pandemi covid-19 terhadap audit delay. Populasi penelitian adalah perusahaan jasa sektor transportasi yang terdaftar di BEI pada tahun 2018-2020 sebanyak 120 perusahaan, dengan sampel penelitian sebanyak 66 perusahaan. Metode pengambilan sampel menggunakan metode purposive sampling dan Analisa data menggunakan analisis regresi berganda. Pengolahan data menggunakan SPSS versi 26. Hasil penelitian m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…During the COVID-19 pandemic, multiple regression analysis results affirm that audit opinion still does not have an influence on audit delay, indicating that the type of opinion on audited financial reports does not affect how quickly or slowly the Audit Delay Analysis Before and During the Covid-19 Pandemic 636 reports are published. Additionally, differences in the audit process before and during the pandemic provide important context for understanding these findings, considering the pandemic's impact on audit methods and significant external factors affecting delays in financial report publication (Manajang & Yohanes, 2022). H5 and H6 are rejected, not in line with findings from some previous studies, but these results are consistent with certain research indicating that audit opinion does not have a significant influence on audit delay, both before and during the COVID-19 pandemic.…”
Section: Acceptedsupporting
confidence: 67%
“…During the COVID-19 pandemic, multiple regression analysis results affirm that audit opinion still does not have an influence on audit delay, indicating that the type of opinion on audited financial reports does not affect how quickly or slowly the Audit Delay Analysis Before and During the Covid-19 Pandemic 636 reports are published. Additionally, differences in the audit process before and during the pandemic provide important context for understanding these findings, considering the pandemic's impact on audit methods and significant external factors affecting delays in financial report publication (Manajang & Yohanes, 2022). H5 and H6 are rejected, not in line with findings from some previous studies, but these results are consistent with certain research indicating that audit opinion does not have a significant influence on audit delay, both before and during the COVID-19 pandemic.…”
Section: Acceptedsupporting
confidence: 67%
“…Research (Hasibuan & Abdurahim, 2017) the complexity of the examination object will not affect the audit delay if it uses qualified external auditors because a qualified Public Accounting Firm will develop its SDM with adequate competence. Research (Manajang & Yohanes, 2022) found that using external auditors with sufficient experience will certainly shorten audit delays even though the company's complexity is relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the research of (Dewi & Wahyuni, 2021), which states the positive and significant influence of the company's complexity on audit delay. However, these studies are inversely opposed to the research (Manajang & Yohanes, 2022), which states that the company's complexity does not affect audit delay. This study will examine the factors that cause audit delays.…”
Section: Introduce the Problemmentioning
confidence: 91%
“…The size of the company negatively and significantly affects audit delay. Then, in opinion, (Manajang & Yohanes, 2022) states that the size of the company does not influence audit delay.…”
Section: The Effect Of Company Size On Audit Delay With the Role Of M...mentioning
confidence: 99%